Answer:
b = 1, c = -1 and d = 4
Step-by-step explanation:
To solve this question the rule of multiplicity of a polynomial is to be followed.
If the multiplicity of a polynomial is even at a point, graph of the polynomial will touch the x-axis.
If the multiplicity of the polynomial is odd, graph will cross the x-axis at that point.
From the graph of function 'f',
f(x) = (x - b)(x - c)²(x - d)³
Since, graph of the function 'f' crosses x-axis at x = 1 and x = 4, multiplicity will be odd and touches the x-axis at x = -1 multiplicity will be even.
So the function will be,
f(x) = (x - 1)[x - (-1)]²(x - 4)³
Therefore, b = 1, c = -1 and d = 4 will be the answer.
3<em>x</em> + 120° + <em>x</em> + 120° = 360°
4<em>x</em> + 240° = 360°
4<em>x</em> = 120°
<em>x</em> = 30°
<em>y</em> = 1/2 (3<em>x</em> - <em>x</em>)
<em>y</em> = 1/2 (90° - 30°)
<em>y</em> = 1/2 × 60°
<em>y</em> = 30°
Answer:
-5/12
Step-by-step explanation:
Solve for x by simplifying both sides of the equation, then isolating the variable.
Answer:
3.) 4
4.) 4j=44
4j/4=44/4
j=11
Pls mark Brainliest :)
Step-by-step explanation: